Effectiveness of a Lifestyle Change Program on Insulin Resistance in Yaquis Indigenous Populations in Sonora, Mexico: PREVISY - Castro Juarez, Alejandro Arturo; Urquidez Romero, Rene; Serna Gutiérrez, Araceli; Alemán Mateo, Heliodoro; Gallegos Aguilar, Ana Cristina; Dórame López, Norma Alicia; Valenzuela Sánchez, Abraham; Valenzuela Guzmán, Diana Marcela; Díaz Zavala, Rolando Giovanni; Esparza Romero, Julián (2023)
Objective: To evaluate the effectiveness of the healthy lifestyle promotion program for Yaquis (PREVISY) on insulin resistance in the short- and medium-term periods in adults who are overweight/obese and have an increased risk for diabetes.